SOSIALISASI MENINGKATKAN KESADARAN MASYARAKAT DALAM MENCEGAH KEBOCORAN DATA NASABAH PERBANKAN DIGITAL MELALUI PESAN PHISHING DI ERA DIGITALISASI - Rismasari, Dini Aprilia; Wikartika, Ira (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2025)
The rapid advancement of technology and information has brought special attention to the security of digital banking customer data. Personal data leakage can have a significant negative impact, both for individuals and financial institutions. One of the causes of data leakage is cyber-attacks, such as phishing. Therefore, steps are needed that can be applied to the community as a form of self-prevention from these threats. The method that can be applied is through educational socialization activities that provide understanding in the form of material, case studies, and discussions (questions and answers). The purpose of this activity is to increase public awareness about the importance of protecting personal data from data leakage caused by cyber-attacks (phishing). The success of this socialization activity was measured using a questionnaire distributed to 30 participants. The results of the questionnaire showed that before the implementation of this socialization activity, only about 10% of participants had understood and understood the dangers of phishing, while the other 90% of participants only knew the meaning of the word phishing itself. Therefore, this socialization activity received a positive response based on the diagram of the questionnaire results which showed that the quality of the content and delivery of material during the socialization activity received a positive assessment from the community. This socialization activity also brought benefits and positive influences to the community, such as 26.7% of participants gained additional knowledge about the dangers of phishing, 30% of participants could become more aware of the threat of phishing so they could avoid it, and 43.3% of other participants could feel safe and more confident to use digital banking applications (mobile banking). All socialization participants gave positive feedback on the socialization activities